2017
DOI: 10.5603/arm.2017.0015
|View full text |Cite
|
Sign up to set email alerts
|

Searching Online for Health-Related Information by People Suffering from Respiratory Allergy and Asthma: The Results of a Survey Study

Abstract: Introduction: The objective of the study was to compare online behaviour in groups of persons suffering from respiratory allergy and/or asthma and in the reference group. Material and methods: Comparative analysis of two independent questionnaire studies. Study A was carried out in the Masovian Voivodeship, Poland in 2013. As many as 1,728 questionnaires were collected and 51 respondents were selected for analysis (study A, reference group). Study B was carried out in 2014 in a group of 59 patients of the outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…Thirdly, although online health information could be an important source of guidance for parents—not least given its accessibility—its current role and effect may be ambiguous. In accordance with prior findings on parental (digital) health information behavior, parents in this study reported frequently using digital ECAP sources, yet ranked digital sources least trusted of the different sources ( 19 , 40 , 51 , 52 ). In our study, this was often justified in terms of “anyone could write anything on the internet”.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Thirdly, although online health information could be an important source of guidance for parents—not least given its accessibility—its current role and effect may be ambiguous. In accordance with prior findings on parental (digital) health information behavior, parents in this study reported frequently using digital ECAP sources, yet ranked digital sources least trusted of the different sources ( 19 , 40 , 51 , 52 ). In our study, this was often justified in terms of “anyone could write anything on the internet”.…”
Section: Discussionsupporting
confidence: 90%
“…In accordance with prior findings on parental (digital) health information behavior, parents in this study reported frequently using digital ECAP sources, yet ranked digital sources least trusted of the different sources (19,40,51,52). In our study, this was often justified in terms of "anyone could write anything on the internet".…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The role of an HE comprises an integral part of integrated healthcare in this era of globalization and digitalization. One very dangerous measure undertaken by the patients themselves is the so-called self-treatment, by using over-the-counter (OTC) medications [ 31 ], homeopathy [ 32 ], and obtaining medical information from unreliable Internet sources [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using the Internet to communicate with the target group reduces the costs and allows for the use of more interactive materials in comparison to traditional methods. Moreover, the Internet is the main source of information for the target group (22).…”
Section: Limitations and Strengths Of The Projectmentioning
confidence: 99%